Pelatihan Implementasi IoT untuk Monitoring dan Otomasi Tanaman Lada di SMK SMTI Bandar Lampung dalam Mendukung Pertanian Berbasis Teknologi - Aryanto Aryanto; M. Herly Pratama (Jurnal Masyarakat Mengabdi Nusantara, 2024)
The Internet of Things (IoT) has revolutionized agricultural practices by offering real-time monitoring, resource management, and process automation. In Lampung, Indonesia, pepper farming faces challenges such as pests, diseases, and inefficient water usage, hindering productivity. This community engagement program focuses on training vocational school (SMK SMTI Bandar Lampung) students in IoT-based smart farming solutions tailored to pepper plantations. The program employs LoRa-based IoT platforms and automatic irrigation systems to enhance agricultural efficiency and sustainability. By integrating theory and hands-on application, students gain critical digital and technical skills, contributing to the development of a sustainable agricultural ecosystem. This initiative also addresses technological literacy gaps, empowering future generations to embrace innovative approaches for agricultural improvement.